2015
DOI: 10.1007/jhep02(2015)103
|View full text |Cite
|
Sign up to set email alerts
|

Holographic thermalization with a chemical potential from Born-Infeld electrodynamics

Abstract: The problem of holographic thermalization in the framework of Einstein gravity coupled to Born-Infeld nonlinear electrodynamics is investigated. We use equal time two-point correlation functions and expectation values of Wilson loop operators in the boundary quantum field theory as probes of thermalization, which have dual gravity descriptions in terms of geodesic lengths and minimal area surfaces in the bulk spacetime. The full range of values of the chemical potential per temperature ratio µ/T on the boundar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 108 publications
(208 reference statements)
1
31
0
2
Order By: Relevance
“…It is from this point on that the Vaiyda spacetime makes a full-fledged appearance as a community work horse of holographic thermalization. A significant portion of these previous works has been dedicated to understanding the thermalization of various quantum quenches, some examples are [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. These examples cover a wide range of AdS Vaidya setups from the addition of charge (Reissner-Nordstrom) to modified gravity theories such as Gauss-Bonnet gravity.…”
Section: Introductionmentioning
confidence: 99%
“…It is from this point on that the Vaiyda spacetime makes a full-fledged appearance as a community work horse of holographic thermalization. A significant portion of these previous works has been dedicated to understanding the thermalization of various quantum quenches, some examples are [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. These examples cover a wide range of AdS Vaidya setups from the addition of charge (Reissner-Nordstrom) to modified gravity theories such as Gauss-Bonnet gravity.…”
Section: Introductionmentioning
confidence: 99%
“…To probe these fascinating phenomena in field theory, one should employ some non-local observables such as equal time two point correlation function for a scalar operator, Wilson loop, and holographic entanglement entropy, which are dual to the geodesic length, minimal area, and minimal volume individually in the saddle point approximation. It has been shown that these observables can probe the nonequilibrium thermalization behavior [4][5][6][7][8][9][10][11][12][13][14][15], superconducting phase transition [16][17][18][19][20][21][22][23], and cosmological singularity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomena is the same behavior as in the case of other charged black holes. For those solutions also, one could see that charge always slows down the thermalization process, for instance the case in four dimensional background which has been addressed in [52].…”
Section: B Hee and Hc In The Neutral Massive Btz Black Holementioning
confidence: 93%